Convergence through the eyes of managers and employees of Belarusian media: on materials of the expert survey - Meleshevich, Raisa I. (Journal of the Belarusian State University. Journalism, 2019)
The results of the expert survey among mass media chief and deputy editors, heads of departments and experienced Belarusian media journalists are considered in this article. In all, 51 respondents were interviewed in November 2018. The studied subjects are: the way media convergence is perceived and undergoing changes in mass media and in the work of journalists due to the rapid development of new technology. It is inferred from the analysed responses that respondents see the importance of content placement options and providing special training in professional work in the Internet. The analysis of the results of the survey indicates the ever-growing attention of Belarusian media managers towards the information placed in social media, through which brand recognition and growth in the number of subscribers is brought. The value of the research results lies in reconsidering the paradigm of education and recognising the vital importance of specialisttraining programmes aimed at designing digital era journalists. Respectively, web-journalists and social media editors are in exceptional demand nowadays.
Keywords: journalism; convergence; expert survey; social networks; user content